Determinants of Stigma Toward People Living With HIV/AIDS: A Cross-Sectional Study - Hidayatul Rahmi Hidayatul; Rebbi Permata Sari (RRZ Scientific Publishing, 2023)
HIV/AIDS stigma is a major issue for people living with HIV/AIDS (PLWHA) around the world. It is the most significant obstacle to HIV prevention, treatment, care, and support. This study aims to determine the determinants of stigma toward PLHA at the Kuranji Health Center, Padang, Indonesia. A cross-sectional study was conducted from November 2022 to February 2023. The respondents of the study were people who were domiciled in the working area of the Kuranji Health Center, aged 15–60 years, and were willing to sign an informed consent. We used purposive sampling techniques and questionnaires to collect data. The data were analyzed using descriptive analysis and the chi-square test. Overall, the prevalence of negative stigma was found to be 85.6%. Bivariate analysis showed a significant correlation between knowledge (p = 0.020), perception (p = 0.000), attitude (p = 0.000), and stigma among PLHA. Our findings suggested that providing culturally congruent education and training about HIV and care and promoting policies protecting PLWHA may massively reduce HIV-related stigma toward PLWHA. Keywords: Stigma, HIV/AIDS, Knowledge, Perception, Attitude